2010
DOI: 10.1590/s0100-204x2010001200023
|View full text |Cite
|
Sign up to set email alerts
|

Milk flow, teat morphology and subclinical mastitis prevalence in Gir cows

Abstract: -The aim of this work was to evaluate the association between milk flow, teat morphological measurements and subclinical mastitis prevalence in Gir cows. Eighty cows in the 2 nd and 3 rd lactations, with 90 to 200 days of lactation, were divided according to milk flow during milking into fast or slow groups. Teat morphometry was assessed by ultrasound scanning of the right anterior teat and external measurements. Milk samples were collected for somatic cells count (SCC) and microbiological culture. The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 22 publications
2
12
0
2
Order By: Relevance
“…Contrary to our findings, the coefficients of the correlations of the milk flow rate with the teat length and teat diameter were insignificant (18). On the other hand, on the basis of their comparison of slow and fast milked cattle, one study reported that the cattle, which were milked slowly, had a greater teat length and teat diameter (24).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our findings, the coefficients of the correlations of the milk flow rate with the teat length and teat diameter were insignificant (18). On the other hand, on the basis of their comparison of slow and fast milked cattle, one study reported that the cattle, which were milked slowly, had a greater teat length and teat diameter (24).…”
Section: Discussionmentioning
confidence: 99%
“…No evidence for this has yet been found for dairy buffaloes. Previously, a smaller teat-end to floor distance was shown to be associated with increased risk of SCC or IMI in dairy cows (Porcionato et al 2010;Singh et al 2014).…”
Section: Teat Morphometry and Quarter Healthmentioning
confidence: 99%
“…The breed has been selected for increased milk production, but studies evaluating parameters and risk factors for mastitis in Dairy Gyr females are sparse. However, some authors recently reported a high prevalence of subclinical mastitis in herds of this breed (Porcionato et al 2010;Malek dos Reis et al 2011), possibly as a consequence of exclusive selection for increased milk production. In this respect, studies investigating indicator traits of mastitis such as SCC and EC, as well as their association with milk production and composition, are important.…”
Section: Introductionmentioning
confidence: 99%